Manley's technology of biscuits, crackers and cookies - Manley, Duncan (Woodhead Publishing Series in Food Science, Technology and Nutrition, 2011)
Eight expert authors have joined Duncan Manley to produce the new edition of this standard industry reference. Substantially revised and updated, it is now some 25% longer than the previous edition. It remains an essential guide for those seeking to improve efficiency and encourage best practice in biscuit, cookie and cracker manufacturing plants